Search for High Energy Skimming Neutrinos at a Surface Detector Array - Thuan, Vo Van; Khanh, Hoang Van; Diep, Pham Ngoc (Communications in Physics, 2012)
In the present study we propose a new method for detectionof high energy cosmological muon neutrinos by transition radiations at amedium interface. The emerging electro-magnetic radiations induced by earth-skimming heavy charged leptons are able to trigger a few of aligned neighboringlocal water Cherenkov stations at a surface detector array similar tothe Pierre Auger Observatory. The estimation applied tothe model of Gamma Ray Burst induced neutrino fluxes and the spherical earth surface shows a competitive rate of muonneutrino events in the energy range below the GZK cut-off.